From information-poverty to information rich: leT as enabler - Kamba, Manir Abdullahi; Mansor, Yushiana (2010)
This paper highlights on the issue of information poverty in the Muslim world and strategize the use of leT in moving towards information-rich society. The potentials that can be derived from leT in the development of Muslim world are discussed. The paper also outlined the challenges that deter the Muslim world from information-empowerment. Factors that hinder the Muslim world to migrate from digital gap to digital inclusion are discussed. Furthermore, the paper concludes that the developments of leT and digital technologies if properly applied by Muslim world can lead them to be part of the information society and consequently become information power societies. This can also lead to digital inclusion, which will have impact on the empowerment of the Muslim ummah.